Exploring the Determinants of Student Spending Behaviour at UiTM Terengganu - Enche Rusmayady, Nur Diana Syahirah; Zakaria, Ain Zulaikha; Abd Ghani, Nurshazwani; Akmal Apandi, Muhammad Akif; Amirruddin, Nor Amirah Farhanah; Mat, Khalid Amin; Shariff, Anita Md. (Journal of Islamic, Social, Economics and Development, 2025)
This study investigates the key factors influencing student spending behaviour at Universiti Teknologi MARA (UiTM) Terengganu, focusing on parental income, peer pressure, social status, and promotional strategies. Using a quantitative approach, data were collected from 107 students through a structured questionnaire and analysed using SPSS. The results reveal that social status and parental income are the most significant predictors of spending behaviour, while peer pressure and promotional tactics show moderate but less predictive influence. These findings highlight the importance of socioeconomic background and social identity in shaping financial decisions among university students. The study underscores the need for targeted financial literacy initiatives that incorporate cultural and religious values to promote responsible spending habits.